Simulation mechanism oscillations pressure vibration burning in low emission combustion chamber gas-turbine units - Ясиніцький, Е.П.; Торхов, М.І.; Лозня, С.В.; Налісний, М.Б. (Proceedings of National Aviation University (archive), 2006)
Mathematical modelling method of the pressure self-oscillations mechanism at vibrating burning in low emission combustion chambers of the gas-turbine units is offered.